Composite and nanocomposite films based on amaranth biopolymers - Condes, María Cecilia (2018)
The use of amaranth starch granules and nanocrystals as possible reinforcement of amaranth 17 proteins films was analyzed. Starch granules and protein isolates were extracted of amaranth 18 grain, and nanocrystals were prepared by acidic hydrolysis from starch. Films were prepared 19 by casting aqueous dispersions containing amaranth protein isolate (API, 5% w/v), glycerol 20 (1.25 % w/v) and different concentrations of starch granules (0 to 30 wt% relative to API) 21 and nanocrystals (0 to 12 wt% relative to API). All films were homogeneous, translucent 22 and slightly brownish, with a general visual appearance similar to the control amaranth 23 protein film. While it was possible to prepare films in which the starch granules retain their 24 native structure after being processed, the presence of these particles did not improve the film 25 properties. Only the addition of starch nanocrystals improved their tensile strength and 26 water vapour permeability as well as their water susceptibility, probably due to their 27 nanosize, uniform distribution and the strong interactions that developed with protein matrix.